Hippocrates, On the art of medicine - Mann, Joel Eryn, 1975- (Studies in Ancient Medicine, 2012)
On the art of medicine , or de Arte , embodies as perhaps no other ancient text the full flower of the sophistic movement of the fifth century BCE. It is a rhetorical epideixis in which forensic oratory, philosophy, and medicine are woven into an ambitious display of sophistic polymathy. Unlike much previous scholarship, however, this book does not dismiss de Arte as "merely" rhetorical. Its analysis of the author's philosophical and medical views reveals that he strove to promote a consistent and rationally grounded system capable of responding to theoretical and practical criticisms levied by those who would deny that there was such a thing as medicine or technē at all.